Microsurgical Denervation of the Spermatic Cord: A Historical Perspective and Recent Developments. (4th January 2022) - Sun, Helen H.; Tay, Kimberly S.; Jesse, Erin; Muncey, Wade; Loeb, Aram; Thirumavalavan, Nannan
Abstract: Introduction: The management of chronic scrotal pain is long and varied, with historical treatment algorithms typically ending with orchiectomy. Microsurgical denervation of the spermatic cord (MDSC) is a testicle-sparing option for patients who have failed conservative treatment options and over its forty-year history has seen many technical refinements. Objectives: To review the history and development of MDSC and discuss the outcomes of different surgical techniques. Methods: A literature review using PubMed and Google Scholar was conducted to identify studies pertaining to surgical treatment of CSP, MDSC, and outcomes. Search terms included "chronic, " "scrotal pain, " "orchialgia, " "spermatic cord, " "denervation, " and "microsurgery." Results: We included 21 case reports and series since the first seminal paper describing MDSC technique in 1978. Additional studies that challenged existing conventions or described novel techniques are also discussed. The current standard procedure utilizes a subinguinal incision and a surgical microscope. Open, robotic, and laparoscopic approaches to MDSC have been described, but access to minimally invasive instruments may be limited outside of developed nations. Pain reduction following preoperative spermatic cord predicts success of MDSC. Methods for identifying and preserving the testicular and deferential arteries vary depending on surgeon preference but appear to have comparable outcomes. Future developments in MDSC involve targeted denervation, minimizing collateral thermal injury, and alternative techniques to visualize arterial supply. Conclusion: For patients suffering from CSP, MDSC is a well-studied technique that may offer appropriately selected patients' relief. Future investigation comparing targeted vs full MDSC as well as in vivo study of new techniques are needed to continue to improve outcomes.